Polyphenolic Characterization of Merlot, Tannat and Syrah Skin Extracts at Different Degrees of Maturity and Anti-Inflammatory Potential in RAW 264.7 Cells - Nawel Benbouguerra (Foods, 2021)
(1) Background: Both sensory quality and healthy attributes of Vitis vinifera grapes used for winemaking are closely related with the polyphenolic composition of their skins. (2) Methods: In this study, the polyphenolic characterization (flavan-3-ols, procyanidins, flavonols, stilbenes, anthocyanins) was investigated by ultra performance liquid chromatography coupled to a triple quadrupole mass spectrometer (UPLC-QqQ-MS). Skins from Vitis vinifera Merlot, Tannat, and Syrah red grape varieties cultivated in the south of France at different stages of ripening in 2018 were used. The anti-inflammatory and the antioxidant potential of the extracts were evaluated by the measure of nitric oxide (NO) and the intracellular reactive oxygen species production (ROS) in lipopolysaccharide (LPS)-stimulated macrophages. (3) Results: 41 polyphenols were quantified in all samples. Generally, the flavan-3-ol and procyanidin content decreased during ripening whereas the anthocyanins and stilbenes increased. In addition, as a novelty of this work, a wide identification and characterization of monomeric and oligomeric stilbenes was assessed by using authentic standards isolated in our laboratory, some of them (parthenocissin A and miyabenol C) reported for the first time in Merlot, Tannat and Syrah cultivars. The before-veraison skin extracts of all studied varieties, exhibited higher NO and ROS productions inhibition (>50%) proving both antioxidant and anti-inflammatory properties.